Psycho-educational group leaders through the homeroom approach: A systematic literature review - Nuha, Moch. Syihabudin; Indreswari, Henny; Bariyyah, Khairul (ProGCouns: Journal of Professionals in Guidance and Counseling, 2024)
Guidance and counseling services can be done through the form of individual or group. A group shall be led by a counselor who has been previously trained in guidance and counseling. A leader must choose a leadership style with priority given to the achievement of goals within the group such as achieving cohesion within the group. The homeroom approach is how a counselor is able to create a group atmosphere of intervention, like a family atmosphere or a home atmosphere. The study aimed to review the reseach of homeroom intervention in guidance and counseling. The literature review is carried out in five stages: formulation of research questions, search for literature, processing of data, and assessment of the quality of filtering received and not received. A total of 100 articles were identified and subjected to PRISMA analysis, resulting in the selection of 12 articles for further in-depth examination. The criteria for articles included discussions on group leadership, counseling groups, strategies in group leadership, targeting students and guidance and counseling teachers in 2013-2023. The results showed that the homeroom approach can be considered as one of the group leader's qualifications. A group leader must have the ability to listen actively, receive, pay attention, create a warm and welcoming atmosphere, connect among members. A homeroom approach can facilitate the group leader to create an atmosphere of warm, welcoming, safe and comfortable within the group dynamics.